STUDY OF THE EFFECT OF ADHESIVE SUBSTANCES ON PAPER STRENGTH PROPERTIES - Aliyeva, Nargiza; Eshbaeva , Ulbosin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, modified cationic starch (MCS) containing 80 percent of cotton cellulose, 20 percent of polyester (lavsan) fiber waste, carboxyl methyl cellulose (NaKMS) glue in the second stage, and acrylic emulsion (AE) in the third stage are 0.5 to 2 percent of the paper pulp. Paper samples were taken by adding up to .5% and the obtained paper samples were comparatively analyzed. The results showed that the quality indicators of the paper samples improved by 15%.